2015
DOI: 10.4184/asj.2015.9.4.495
|View full text |Cite
|
Sign up to set email alerts
|

Rat Notochordal Cells Undergo Premature Stress-Induced Senescence by High Glucose

Abstract: Study DesignIn vitro cell culture.PurposeThe purpose of the study was to investigate the effect of high glucose on premature stress-induced senescence of rat notochordal cells.Overview of LiteratureGlucose-mediated increase of oxidative stress is a major causative factor for the development of diseases associated with diabetes mellitus such as senescence. However, no information is available for the effect of high glucose on premature stress-induced senescence of rat notochordal cells.MethodsNotochordal cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…The present study found that high glucose obviously increased intracellular ROS generation and activated the downstream NF-κB pathway in NP cells, which indicates that high glucose induced an oxidative stress reaction in NP cells. This result is consistent with previous studies that demonstrated that oxidative stress may be a potential mechanism for high glucose-related disc degenerative changes [9, 33]. However, we found that N-CDH overexpression decreased ROS generation and NF-κB pathway activity in NP cells under the high glucose condition, which indicates that N-CDH may suppress high glucose-induced cellular oxidative stress in NP cells.…”
Section: Discussionsupporting
confidence: 78%
“…The present study found that high glucose obviously increased intracellular ROS generation and activated the downstream NF-κB pathway in NP cells, which indicates that high glucose induced an oxidative stress reaction in NP cells. This result is consistent with previous studies that demonstrated that oxidative stress may be a potential mechanism for high glucose-related disc degenerative changes [9, 33]. However, we found that N-CDH overexpression decreased ROS generation and NF-κB pathway activity in NP cells under the high glucose condition, which indicates that N-CDH may suppress high glucose-induced cellular oxidative stress in NP cells.…”
Section: Discussionsupporting
confidence: 78%
“…Given that NNPC are more metabolically active and sensitive to nutrient disturbances [Guehring et al, 2009;Park et al, 2015], the possibility exists that the notochordal cell resources are exhausted by excessive apoptosis or senescence while the cells attracted from the CEP mediate the fibrocartilaginous changes within the NP [Kim et al, 2003[Kim et al, , 2009]. Another limitation of our hypothesis is that the genetic inheritance of IVD degeneration is not covered by the equation P e = P m + P v .…”
Section: Significance and Limitations Of The Hypothesismentioning
confidence: 88%
“…During the transportation of electrons, a small proportion of electrons (1%–3%) leak and reduce O 2 to O 2 − rather than H 2 O [53, 54]. The mitochondrion-dependent ROS production has been reported in various disc cells derived from different species (Figure 1), including human NP cells, human AF cells, rat AF cells, rat notochordal cells, and rabbit NP cells [5560]. Nonmitochondrial oxygen consumption through nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) or xanthine oxidase (XO) is one other main ROS production site (Figure 1) [61, 62].…”
Section: Ros Production In Healthy Ivdsmentioning
confidence: 99%
“…In this microenvironment, various exogenous stimuli, such as mechanical loading, high oxygen tension, high glucose stress, and proinflammatory cytokines, increase ROS production in disc cells (Figure 2). Furthermore, ROS themselves also enhance ROS production in disc cells, forming a positive feedback loop [14, 15, 2024, 36, 44, 5660]. …”
Section: Disturbed Redox Homeostasis In the Microenvironment Of Dementioning
confidence: 99%
See 1 more Smart Citation